Is there respectful maternity care in Poland? Women's views about care during labor and birth - Barbara Baranowska; Antonina Doroszewska; Urszula Kubicka-Kraszyńska; Joanna Pietrusiewicz; Iwona Adamska-Sala; Anna Kajdy; Dorota Sys; Urszula Tataj-Puzyna; Grażyna Bączek; Susan Crowther (BMC, 2019)
Abstract Background Abuse against women in labor starts with subtle forms of discrimination that can turn into overt violence. Therefore it is crucial to work towards prevention and elimination of disrespect and ill-treatment in medical facility perinatal care in which staff allows such abuse. The aim of the study was to analyze the experiences of women related to perinatal care. Special emphasis was put on experiences that had traits indicating disrespectful and offensive care during childbirth in medical facilities providing perinatal care. Methods This was a cross-sectional survey. A questionnaire was prepared for respondents who gave birth in medical facilities. Information about the study was posted on the website of a non-governmental foundation dealing with projects aimed at improving perinatal care. The respondents gave online consent for processing the submitted data. 8378 questionnaires were submitted. The study was carried out between February 06 and March 20, 2018. The results were analyzed using the Chi-square independence test. The analysis was carried out at the significance level of 0.05 in Excel, R and SPSS. Results During their hospital stay, 81% of women in the study experienced violence or abuse from medical staff on at least one occasion. The most common abuse was having medical procedures without prior consent. Inappropriate comments made by staff related to their own or a woman's situation were reported in 25% of situations, whilst 20% of women experienced nonchalant treatment. In the study 19.3% of women reported that the staff did not properly care for their intimacy and 1.7% of the respondents said that the worst treatment was related to feeling anonymous in the hospital. Conclusions The study shows that during Polish perinatal care women experience disrespectful and abusive care. Most abuse and disrespect involved violation of the right to privacy, the right to information, the right to equal treatment, and the right to freedom from violence. The low awareness of abuses and complaints reported in the study may result from women's ignorance about relevant laws related to human rights.